Expansionary fiscal consolidations in Europe: new evidence - Afonso, António (2010)
In order to assess the existence of expansionary fiscal consolidations in Europe, panel data models for private consumption are estimated for the EU15 countries, using annual data over the period 1970-2005. Three alternative approaches to determine fiscal episodes are used, and the level of government indebtedness is also taken into account. The results show some evidence in favour of the existence of expansionary fiscal consolidations, for a few budgetary spending items (general government final consumption, social transfers, and taxes), depending on the specification and on the time span used. On the other hand, the possibility of asymmetric effects of fiscal episodes does not seem to be corroborated by the results.